Pemberdayaan UMKM Desa Lingga Melalui Legalitas Nomor Induk Berusaha Berbasis SDGs - Triani, Sandrina Marsha; Malini, Helma; Zhafirah, Nony Ulya’ Sari; Yulia, Putri Meyke; Lestari, Nuraini; Alfanny, Nabila Alifia (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Lingga Village, Kubu Raya Regency, face challenges of low digital literacy and limited awareness of business legality, resulting in the absence of Business Identification Numbers (NIB) and restricted access to government support. To address this issue, a community service program was implemented using Service Learning, Technology Transfer, and Community Development approaches through stages of material preparation, socialization, technical assistance with the Online Single Submission (OSS) system, and evaluation. Among 15 participants, 14 (90%) successfully obtained NIBs, while understanding of business legality increased from 10% before the program to 90% afterward. These results indicate that a combined strategy of mentoring and hands-on practice effectively reduces administrative barriers and overcomes digital skill limitations. Formal business legality not only strengthens MSMEs’ credibility with consumers and financial institutions but also expands access to financing and government programs. This finding highlights the role of legality assistance as a catalyst for integrating MSMEs into the formal economy and contributes to the achievement of Sustainable Development Goal (SDG) 8 on inclusive and sustainable economic growth.